STUDIES ON THE WATER USE EFFICIENCY AND NUTRIENT UPTAKE BY RICE UNDER SYSTEM OF INTENSIFICATION - CHOWDHURY, MD. RITON; KUMAR, VINOD; SATTAR, ABDUS; BRAHMACHARI, KOUSHIK (The Bioscan, 2014)
All the growth and developmental parameters viz. plant height, leaf area index, crop growth rate (CGR), panicle m-2, grain weight per panicle, grain and straw yield, NPK content in grain and straw as well as nutrient uptake were better influenced by 2.5 cm irrigation 0 days after disappearance of ponded water (DAD) over 6 DAD but were at par with 3 DAD. The test weight was not influenced by irrigation levels. Water-use efficiency (WUE) was favourably influenced by 2.5 cm irrigation 3 DAD over 0 DAD but was at par with 6 DAD. Final soil fertility status (N, P2O5 and K2O ha-1) decreased with increasing levels of irrigation. All the growth and development parameters, grain and straw yield, WUE, NPK content in grain and straw, nutrient uptake , were favourably influenced by 10 t FYM ha-1 + 120 kg N, 60 kg P2O5 and 40 kg K2O ha-1 (F2) over all the nutrient levels. Both the gross and net return were significantly higher at 0 DAD over 6 DAD but were at par with 3 DAD while, F2 was significantly higher over all the nutrient levels. The highest return per rupee of investment was recorded at 2.5 cm irrigation 3 DAD while, it was significantly higher at F1 (120 kg N, 60 kg P2O5 and 40 kg K2O ha-1) over all the nutrient levels but was at par with F2 level.